Hand weeding tools in vegetable production systems: an agronomic, ergonomic and economic evaluation. Issue 4 (4th July 2022) - Tiwari, Sita; Sindel, B.M.; Smart, N.; Coleman, M.J.; Fyfe, C.; Lawlor, C.; Vo, B.; Kristiansen, P.
ABSTRACT: Hand weeding is a common method of weed control on vegetable farms, especially in developing countries. It requires considerable physical labour and is a significant economic burden, yet comparative studies on hand weeding tools are rare. We evaluated the agronomic, ergonomic and economic performance of four hand weeding tools (and unweeded control) at two sites and two weed ages. Agronomic efficiency was evaluated based on the reduction in weed load from pre-weeding to post-weeding, economic efficiency based on the time taken to weed, and ergonomic efficiency based on heart rate and energy expenditure of the tool operator. Among the tools, the chipping hoe provided higher weed control efficiency than the rotating hoe and combined tool, and showed a lower average heart rate and workload than the combined tool. Ergonomic performance was superior in loam soil compared with clay. The light-weight chipping hoe provided better weed control than heavier tools while also reducing the workload of the weeder. Tools did not differ in economic performance, but the cost was 50% higher with late weeding. Viable hand weeding strategies require the optimization of tools for ergonomic performance and careful attention to timing of operations, thus benefiting economic performance. GRAPHICAL ABSTRACT: UF0001